The precision of DCE-MRI using the tissue homogeneity model with continuous formulation of the perfusion parameters - Bartoš, Michal; Jiřík, Radovan; Kratochvíla, Jiří; Standara, Michal; Starčuk, Zenon; Taxt, Torfinn (Magnetic resonance imaging, 2014)
The present trend in dynamic contrast-enhanced MRI is to increase the number of estimated perfusion parameters using complex pharmacokinetic models. However, less attention is given to the precision analysis of the parameter estimates. In this paper, the distributed capillary adiabatic tissue homogeneity pharmacokinetic model is extended by the bolus arrival time formulated as a free continuous parameter. With the continuous formulation of all perfusion parameters, it is possible to use standard gradient-based optimization algorithms in the approximation of the tissue concentration time sequences. This new six-parameter model is investigated by comparing Monte-Carlo simulations with theoretically derived covariance matrices. The covariance-matrix approach is extended from the usual analysis of the primary perfusion parameters of the pharmacokinetic model to the analysis of the perfusion parameters derived from the primary ones. The results indicate that the precision of the estimated perfusion parameters can be described by the covariance matrix for signal-to-noise ratio higher than~20dB. The application of the new analysis model on a real DCE-MRI data set is also presented.
Keywords: interpretace obrazu počítačem; magnetická rezonanční angiografie; Magnetic Resonance Angiography; počítačová simulace; Image Interpretation, Computer-Assisted; Reproducibility of Results; lidé; Sensitivity and Specificity; vylepšení obrazu; nádory prostaty; senzitivita a specificita; Algorithms; Prostatic Neoplasms; rychlost toku krve; modely kardiovaskulární; Computer Simulation; Blood Flow Velocity; Image Enhancement; reprodukovatelnost výsledků; Male; Perfusion; kontrastní látky; algoritmy; Dynamic contrast-enhanced MRI (DCE-MRI); Parameter estimation; mužské pohlaví; Models, Cardiovascular; Contrast Media; Bolus arrival time; Humans